The Unexamined Identity: Students' Conservative Ideology, Perspectives of Poverty, and Implications for Practice. (2nd October 2021) - Toft, Jessica; Calhoun, Molly
ABSTRACT: Political ideology, shaped by both social identity and policy preferences, may influence how social work students define and approach social justice. This study examines how the political ideology of conservative and moderate social work students relates to their attitudes about the poor, attributions for poverty, and preferred ways to address poverty. Findings demonstrate that those with more conservative ideologies held more negative perspectives of the poor, were more likely to attribute poverty to individual fault, and supported more limited interventions. Unpacking political ideology in the classroom is critical in understanding our power within practice. Further research should consider how social workers' political ideology affects their work with clients and dedication to the social and economic justice mission of social work.